Memória, perdão e promessa: justiça de transição e constitucionalismos transicionais - Tayara Talita Lemos (2017)
During the historical transition from authoritarian or totalitarian regimes to democracy, the Transitional Justice emerged, manifesting itself in a series of judicial and non-judicial approaches that aim to attend the need of reparation of the victims generated by the events that took place during those regimes, which demanded more effectiveness from human rights. In the concept of Transitional Justice is also included the need to rescue memory and history, and their roles in the constructing of democracy and the duty of what we want to call a fair memory. Rescuing memory from a factual concept that composes the collective memoir and counterposes the official discourse should be a task for public institutions along with civil society. This step to an efficient Transitional Justice will be inquired taking into account a few political theories, specifically Hanna Arendts and Paul Ricoeurs philosophy. The object of our analysis will be the conceptual pariticularities developped by both authors, such as the specific connotation given to expressions like forgiveness, promises, factual truth, fundation, history, memory, oblivion and memory duty. The authoritarian experiences that took place in Brazil after the year of 1988, even though their foundational basis was a democratic Constitution, reveal the legacy of officialized institutional violence form the Civil and Military Dictatorship, which minimizes the possibilities of the rising of an effective Transitional Justice. The judicial decisions that correspond to the concepts of amnesty or amnesia, institutional violence, oblivion or minimizing traumatic events policies are part of this heritage, which needs to be overcome, or drafted, in order to build a real democracy. Therefore, the search for the truth and for the States forgiveness, which doesnt correlate to amnesty or oblivion, will be unveiled as an important step in order to announce and fulfill promises. Hence, itll be by demonstrating the pragmatic aspect of memory and forgiveness that the past that doesnt pass will be unrevelled. Transitonal Justice, inserted in a constitutional background, appears as an essential part of the fundational act for democracy and for the building of transitional constitutionalisms that are appropriate for their historical backgrounds.